Case – Renal artery pseudoaneurysm: A life-threatening occurrence following thulium laser lithotripsy - Monteiro, Ajit; Waisanen, Kyle M.; Ermolovich, Eugene V.; Jung, Ichabod S.; Roehmholdt, John M. (Canadian Urological Association Journal, 2021)
Introduction Renal artery pseudoaneurysm post-laser lithotripsy is a rare and potentially life-threatening complication. Traditionally, the most common modalities used for treatment of urinary tract stones were holmium laser lithotripsy and extracorporeal shockwave lithotripsy. However, thulium laser has recently gained momentum in the treatment of urinary tract stones, with increasing use and availability in healthcare systems. We report a case of renal artery pseudoaneurysm post-thulium laser lithotripsy who presented in hemorrhagic shock after ureteral stent removal and was subsequently stabilized by endovascular embolization.